Pengaruh Penggunaan Media Sosial Instagram Terhadap Pemahaman Akhlak pada Mahasiswa PAI Angkatan 2021 di Universitas Ibn Khaldun Bogor - Andestend; Rahmatillah, Intan Nurmala; Rusmana, Indriya (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Understanding morals is one of the important components that students must have in an effort to deepen their knowledge and values ​​of Islamic teachings as the basis of a Muslim's knowledge. There are two factors that can influence each individual's understanding of morals, namely internal factors and external factors. Internal factors come from within students such as thought patterns, attitudes and self-motivation. Meanwhile, external factors include family, school, social environment and social media. Support for achieving understanding of student morals through the social media Instagram can be obtained if students have the ability to act and behave critically, carefully, wisely, think objectively and appreciate the diversity of Islamic information obtained. This research aims to find out whether there is an influence of the use of Instagram media on students' understanding of Islam at Ibn Khaldun University, Bogor. The research method used is a quantitative method. The data collection techniques used were questionnaires and documentation. The analysis technique used by researchers is an inferential statistical analysis technique with an analysis stage in the form of an analysis prerequisite test stage consisting of a normality test and linearity test, hypothesis testing consisting of a simple linear regression analysis test and a t test with the help of the SPSS version 27 application. Results from Research shows that there is an influence of the use of social media on the understanding of morals of PAI students class of 2021 at Ibn Khaldun University, Bogor. The magnitude of the influence that social media has on Islamic understanding shows a figure of 17.9%. Social media has an influence in shaping students' understanding and behavior regarding morals. Students who have good personalities and are not easily influenced by anything can determine their understanding of the information received via Instagram social media.